Learning Genitourinary and Pelvic Imaging - Vilanova, Joan C.; Vilanova, Joan C.; Luna, Antonio.; Luna, Antonio.; Ros, Pablo R.; Ros, Pablo R. (Learning Imaging,, 2012)
This introduction to genitourinary and pelvic radiology is a further volume in the Learning Imaging series. Written in a case-based format, the book is subdivided into ten chapters: kidney; adrenal gland; urinary bladder, collecting system and urethra; prostate and seminal vesicles; scrotum; obstetrics; uterus; cervix and vagina; adnexa and retroperitoneum. Genitourinary radiology has undergone a tremendous change owing to advances in ultrasound, CT and MRI that have redefined our understanding of genitourinary and pelvic pathology. Each chapter includes an introduction and ten case studies with illustrations and comments from anatomical, physiopathological and radiological standpoints and with bibliographic recommendations. Learning Genitourinary and Pelvic Imaging will be of value for radiologists, radiology residents, medical students and anybody else working in genitourinary and pelvic pathology. Learning Imaging is a unique case-based series for those in professional education in general and for physicians in particular.